A Craniometrical Analysis of The Early Bronze Age Dogs from Vučedol site (East Slavonia, Croatia) - Mihelić, Damir (Array, 2013)
During archaeological campaigne on Vučedol site 7 crania and cranial fragments together with 10 halfs of lower jaws were found. Due to existance of crania and lower jaws damages and therefore lack of preserved craniometricalpoints, it was not possible to measure the same craniometrical lengths on all the samples. Apart from craniometrical measurements, 6 craniometrical indices and ratios were calculated. Comparison of calculated values and values of craniometrical indices and ratios identify dog's crania from Vučedol site as dolichocephalic cranial type. Mutual comparison of all analyzed craniometrical values for crania and lower jaws of dog's crania don't show a significant difference in size and ratios of individual measures, nor significant deviation in value of the samples of other Vučedol culture sites. This point out on type of dogs with similar appearance which tallness and form respond to smaller dog's breed, in the first place a type of Croatian sheepdog or Hungarian Mudi.